The efficacy, safety and carry-over effect of diacerein in the treatment of painful knee osteoarthritis: a randomised, double-blind, NSAID-controlled study - Louthrenoo W. (2014)
To evaluate the efficacy, safety and carry-over effect of diacerein, in comparison to piroxicam, in the treatment of Thai patients with symptomatic knee osteoarthritis (OA).